Emerging landscape of circular RNAs in lung cancer. (28th July 2018) - Hu, Wei; Bi, Zhuo-Yue; Chen, Zhen-Long; Liu, Cong; Li, Lin-Lin; Zhang, Feng; Zhou, Qun; Zhu, Wei; Song, Yang-Yi-Yan; Zhan, Bo-Tao; Zhang, Qian; Bi, Yong-Yi; et al.
Abstract: Lung cancer, the leading cause of cancer deaths worldwide, is characterized with malignant cell growth. Advances in next-generation sequencing has helped us further understand RNA and identify novel circular RNAs (circRNAs) that may be useful in the early diagnosis and treatment of lung cancer. Similar to other noncoding RNAs, circRNAs present diverse biological functions in normal and disease states, including various types of cancers. This review focuses mainly on the poorly understood functions of circRNA in lung cancer. This paper also summarizes the recent advances in circRNA biogenesis, analyzes the role of circRNAs in cancers, and discusses the potential mechanisms of circRNAs in lung cancer. Highlights: Classification and underlying mechanisms of circRNA formation. CircRNA profiles, their cellular effects and corresponding mechanisms in lung cancer. Possible mechanisms of circRNAs in lung cancer.